α-Selective Allylation of Azo Compounds Using Allylic Barium Reagents - Yanagisawa, Akira; Jitsukawa, Takuya; Yoshida, Kazuhiro (Synlett, 2013)
The addition of allylic barium reagents to azo compounds was achieved with high α-regioselectivity. The double-bond geometry of allylic barium reagents was retained throughout the reaction at –78 °C and E- or Z-enriched allylic hydrazines were selectively obtained from the corresponding allylic barium reagents. An allylic hydrazine was efficiently converted into an allylic amine by reductive N–N bond cleavage.
Keywords: allylation; allylic amines; azo compounds; barium; hydrazine